Uji Validasi Instrumen Penelitian Model Intention Follow Green Account - Adinda Mutiara Putri Sakhina; Rini Kuswati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to test the construct measurement instruments used in the green account intent research model to ensure that the instruments used in this study are valid and have the ability to accurately measure the various variables included in the model tested by the researcher. Two tests were used to evaluate the instrument: validity test and reliability test. The reliability test uses the composite reliability value and Cronbach alpha, while the validity test is conducted with discriminant and convergent validity tests. This study used 100 respondents as the sample. Non-probability purposive sampling method was used. The SmartPls application was used to conduct data analysis. The result of this study is the obtained measurement accuracy of the instrument in the research model of intention to follow green accounts.